Creating the future of nursing education in Malaysia: envisioning the evolution of e-nursing education in Malaysia / Nanthakumaran Manickam and Ashah Manghanmal - Nanthakumaran, Manickam; Ashah, Manghanmal (Penerbit UiTM (UiTM Press), 2009)
Technology in education has advanced significantly and in tandem with these advances and the nations ICT agenda, nursing education in Malaysia must play its role in application of new technological and pedagogical advances towards achieving a knowledgeable and skillful workforce. A local study was conducted on a group of nursing students (n=58) using the traditional approach and the blended approach in teaching Myocardial Infarction. In the blended approach, an instructional design was used together with face to face interaction. Results showed significant differences in achievement (mean 15.21 and std dev. 2.06) in the group taught with the blended approach. In general these students (Group1) demonstrated positive acceptance of its use as they found this approach different, exciting and interesting. Investigation into educator’s perceptions of the use of instructional technology and a blended approach in nurse education indicated that educators need proper preparation and support in this endeavor. Findings have implications for improving knowledge and use of information technology, for review of the nursing curriculum and for addressing identified institutional and administrative barriers.